PENGARUH MOTIVASI BERWIRAUSAHA DAN KEGIATAN PENYULUHAN KEWIRAUSAHAAN YANG DILAKSANAKAN OLEH DINAS TENAGA KERJA KOTA BATAM TERHADAP MINAT BERWIRAUSAHA DI KOTA BATAM - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to look at the influence of motivation for entrepreneurship and entrepreneurial education to the interest in entrepreneurship. The study was conducted at the Department of Labor in Batam with people who participated in counseling as respondents in this study. The population in this study was 150 respondents. Mechanical sample calculations using formulas slovin, so that the samples obtained a total of 109 respondents. The results showed that entrepreneurship motivation significantly influence the interest in entrepreneurship, this can be seen from the significant value of 0.041, the significance value is less than 0.05. Extension entrepreneurial significant effect on interest in entrepreneurship, this can be seen from the significant value of 0.000, the significance value is less than 0.05. Motivation entrepreneurship and entrepreneurial education simultaneously significant effect on the interest in entrepreneurship, this can be seen from the significant value of 0.000, the significance value is less than 0.05. R square of 0.248 or 24.8%. This means, variable motivation and counseling were able to explain the variable interest in entrepreneurship by 24.8%, while the remaining 75.2% is explained by other factors not included in this study.